Disasterprep: gamified mobile edutainment for future disaster preparedness and resilience - Sakinah Ali Pitchay; Farida Ridzuan; Azni Haslizan Ab Halim; Najwa Hayaati Mohd Alwi (Penerbit Universiti Kebangsaan Malaysia, 2024)
In 2021, Malaysia experienced a significant flood, known as 'the worst flood of the century'. In 2019, a severe haze led to the closure of over 2000 schools. Over half of the surveyed individuals rated their disaster preparedness knowledge as poor or fair. While the government has taken steps to manage disasters, there is still a lack of preparedness at the community level. This research aims to assess the target users' current disaster preparedness knowledge and behaviours. To address this, we develop a user-centred mobile application that combines education and entertainment elements to enhance disaster preparedness and resilience. DisasterPrep introduces a three-dimensional (3D) virtual environment using a metaverse concept, incorporating gamification and user engagement to simulate calamities in Malaysia. The expected outcome of this research is to promote an innovative mobile edutainment application that enhances disaster preparedness and response education. It features interactive modules, gamified challenges, and real-time alerts, supported by a user-friendly interface with quizzes, simulations, and localized risk assessments. Users can explore four main menus—training, flood, earthquake, and disaster outbreak—offering realistic preparation, response, and recovery scenarios. The app includes voiceover options in English and Malay, with e-certificates awarded upon level completion. Usability testing showed improved knowledge, positive behavioural changes, and community resilience. All seven test cases were successfully passed. By leveraging immersive simulations and interactive experiences, DisasterPrep cultivates critical skills, increases engagement, and improves accessibility. Additionally, it supports sustainability through reduced paper use, cost savings, and energy efficiency, ensuring broad accessibility while promoting disaster resilience.